Persepsi Kemanfaatan dan Persepsi Kemudahan pada Minat Membayar PBB Menggunakan Go-Pay dengan Sikap Penggunaan sebagai Variabel Intervening - Dewi Kusuma Wardani; Anita Primastiwi; Hermalia Hermalia (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
This study aims to examine whether the perceived usefulness and perceived convenience affect the interest in paying land and building tax using go-pay through the use attitude as an intervening variable. This research method uses quantitative description methods and primary data using a questionnaire. The study took a sample of 87 respondents who used go-pay and were taxpayers of land and building in Sleman Regency. The sampling technique using convenience sampling technique. Data were collected by leaving a questionnaire in the google form and questionnaire.The results of this study indicate that the perceived usefulness and perceived ease of use have a positive effect on the attitude of use. Perceptions of usefulness, perceived ease of use and attitudes of use have a positive effect on interest in paying land and building taxes using go-pay. perceived usefulness and perceived convenience have a positive effect on interest in paying land and building tax using go-pay through usage attitudes.